Conversion mechanism of a continuous pressure arch structure in strip filling mining - Xiaoping Shao; Long Wang; Xin Li; Zhiyu Fang; Bingchao Zhao; Ershuai Liu; Lang Liu (Arabian Journal of Geosciences, 2021)
Strip mining is the key technology to solve the problem of coal mining under water, so mastering the law of overburden load transfer in strip mining is the key to safe production in working face. We studied it in the context of the shallow seam No. 3 in the Shanghe Coal Mine (northern Shaanxi Province, China) through similarity simulation and field measurement analysis. A theoretical analysis, based on the concept of pressure arch, allowed the establishment of a continuous arch theoretical model for the strip coal pillars (or filling bodies) of the mine. A similar simulation study on strip filling and staged mining has previously shown that, in a first stage, the overlying strata load is mainly transferred to the remaining strip coal pillars; in a second stage, this load is mainly sustained by the odd-numbered strip coal pillars; finally, in a third stage, this load is mainly sustained by the first-stage strip filling body, while the third-stage filling body is not loaded. Our theoretical analysis showed that, during the first stage, the overlying rock load outside the arch was mainly sustained by the arch structure, while that inside of the arch was sustained by the filling body; in the second stage, the arch structure lost stability during the recovery of the even-numbered coal pillars and the arch axis developed upward, leading to the formation of a new arch with an odd number of coal pillars as the arch foot; in the third stage, after the recovery of the odd-numbered coal pillars, a new arch was formed. The arch foot of the new supporting structure was represented by the first-stage filling body; moreover, the load was mainly borne by the second-stage filling body, ensuring the stability of the overburden rock after mining. The theoretical analysis revealed that the pillar or filling body only bears part of the overburden load in strip filling mining. The pillar (filling body) load in correspondence of working face 3216 during each stage of filling was measured and analyzed, proving a continuous arch structure transformation between the pillar and the filling body. Finally, we verified the reliability of the proposed theoretical model.